Sistem Gerak Robot Mainland Surveillance menggunakan Mecanum Wheel sebagai Militer Robot - Fahmizal, Fahmizal; Mayub, Afrizal; Arrofiq, Muhammad (Majalah Ilmiah Teknologi Elektro, 2018)
Robotics in human life is very important. It is also in military sector. Modern countries intensively show of force in high technology robot developed. Indonesia has a special army force with highly military skill called Kopasus. Kopasus is special squad in mainland. Other countries also include robots as additional equipment to personnel. This military robot would help personnel performing surveillance.  In this research, the prototype of surveillance mainland robot has been developed. The prototype could be used by military personnel in surveillance. In order to realize the aim, this research conducts designing of robot movement mechanism as a main  point of view of this research. By using mecanum wheel platform, the surveillance main land robot is expected having navigation capability in all directions.